2010
DOI: 10.1159/000319595
|View full text |Cite
|
Sign up to set email alerts
|

Oral Appliance Therapy versus Nasal Continuous Positive Airway Pressure in Obstructive Sleep Apnea: A Randomized, Placebo-Controlled Trial

Abstract: Background: Previous randomized controlled trials have addressed the efficacy of mandibular advancement devices (MADs) in the treatment of obstructive sleep apnea (OSA). Their common control condition, nasal continuous positive airway pressure (nCPAP), was frequently found to be superior to MAD therapy. However, in most of these studies, only nCPAP was titrated objectively but not MAD. To enable an unbiased comparison between both treatment modalities, the MAD should be titrated objectively as well. Objective:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
194
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(203 citation statements)
references
References 54 publications
5
194
2
2
Order By: Relevance
“…As a further aspect for investigation, more information should be drawn from the amount of the advancement that is required to achieve the best balance between benefit and discomfort, which was shown to be a critical aspect in the OSA literature. 33 Moreover, as a further limitation of this review, it should be noted that the external validity is not optimal due to the poor consistency between the reviewed studies as far as the methodological features are concerned.…”
Section: Discussionmentioning
confidence: 95%
“…As a further aspect for investigation, more information should be drawn from the amount of the advancement that is required to achieve the best balance between benefit and discomfort, which was shown to be a critical aspect in the OSA literature. 33 Moreover, as a further limitation of this review, it should be noted that the external validity is not optimal due to the poor consistency between the reviewed studies as far as the methodological features are concerned.…”
Section: Discussionmentioning
confidence: 95%
“…19,20 Finally, 14 studies were included in this metaanalysis. [10][11][12][13][14][15][21][22][23][24][25][26][27][28] Among these studies, 8 trials had a crossover design, [10][11][12]15,[21][22][23]27 and 6 had a parallel-group design. 13,14,[24][25][26]28 The main characteristics of the included studies are shown in Table 2.…”
Section: Withdrawals and Dropoutsmentioning
confidence: 99%
“…14,22,[24][25][26]28 Adequate method for allocation concealment was applied in 3 trials. 14,27,28 In one trial, 28 the subjects remained blinded to the nature of therapy, and examiner blinding was performed in 3 trials. 22,27,28 The description of follow-up was considered adequate in all included trials.…”
Section: Risk Of Bias In These Trialsmentioning
confidence: 99%
“…In randomized controlled trials comparing both modalities of treatment, CPAP therapy is consistently more effective in reducing sleep disordered breathing events. [6][7][8][9] While CPAP and MAS have similar subjective and cardiovascular outcomes, patients tolerate MAS better. [8][9][10][11] The superior patient satisfaction associated with the use of MAS reflects the relative simplicity and convenience of this form of treatment.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
“…[6][7][8][9]19 Randomized control trials have shown no significant differences in subjective sleepiness and quality of life when comparing CPAP to MAS. 8,20,21 Our study showed an interesting and important finding in terms of daytime sleepiness.…”
mentioning
confidence: 99%